THE HISTORY OF THE RESTORATIONS OF ST. PANTELEIMON'S CHURCH NEAR HALYCH: FROM HISTORY TO NOWADAYS - HUSAK, Andrii (Halych. Scientific work collection, 2019)
This article is dedicated to St. Pantaleon church, a unique monument of Romanesque architecture. It is the sole authentic edifice of the Galician architectural school and a well-preserved one. Having analysed the past of the church, from the time of its founding till today, on the basis of newly discovered sources, I present the history of this temple, its renovations and reconstructions.